2009
DOI: 10.1051/0004-6361/200912762
|View full text |Cite
|
Sign up to set email alerts
|

Local dark matter and dark energy as estimated on a scale of ~1 Mpc in a self-consistent way

Abstract: Context. Dark energy was first detected from large distances on gigaparsec scales. If it is vacuum energy (or Einstein's Λ), it should also exist in very local space. Here we discuss its measurement on megaparsec scales of the Local Group. Aims. We combine the modified Kahn-Woltjer method for the Milky Way-M 31 binary and the HST observations of the expansion flow around the Local Group in order to study in a self-consistent way and simultaneously the local density of dark energy and the dark matter mass conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 30 publications
7
45
0
Order By: Relevance
“…The zero-gravity radius of the Virgo system is about 10 times larger than that of the Local system for which R ZG = 1−1.3 Mpc Chernin et al 2000Chernin et al , 2009. We see here the same factor 10 as for the phase structures of the Virgo and Local systems (Sect.…”
Section: Zero-gravity Radius In the Point-mass Approximationsupporting
confidence: 66%
See 1 more Smart Citation
“…The zero-gravity radius of the Virgo system is about 10 times larger than that of the Local system for which R ZG = 1−1.3 Mpc Chernin et al 2000Chernin et al , 2009. We see here the same factor 10 as for the phase structures of the Virgo and Local systems (Sect.…”
Section: Zero-gravity Radius In the Point-mass Approximationsupporting
confidence: 66%
“…Local dynamical effects of dark energy have been studied by Chernin et al (2000Chernin et al ( , 2009, , Baryshev et al (2001), Karachentsev et al (2003a), Byrd et al (2007), and Teerikorpi et al (2008). For the Local Group and the outflow close to it, we showed that the antigravity produced by the dark energy background exceeds the gravity of the group at distances beyond 1.5 Mpc from the group barycenter.…”
Section: Antigravity In Newtonian Descriptionsupporting
confidence: 56%
“…(3)) used above does not contain any local dark energy term, which would in all cases have a minor effect on systems smaller than galaxy groups (Chernin et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In a weak field situation one may A&A 577, A144 (2015) write (Chernin et al 2009) the force affecting a test particle with mass m as the sum of Newton's gravity force produced by the mass M and Einstein's antigravity force due to DE:…”
Section: Zero-gravity Radius and Einstein-straus Scalementioning
confidence: 99%
“…In regions where the DE dominates the gravitating matter, new structures do not condense and linear perturbations of density decay (or even nonlinear, if sheet-like; Chernin et al 2003). The antigravity of DE also puts an upper limit on the size of a bound system of a certain mass, and it influences dynamic mass determinations, leading to too low a mass Chernin et al (2009Chernin et al ( , 2012.…”
Section: Introductionmentioning
confidence: 99%